2012
DOI: 10.1007/978-3-642-34026-0_44
|View full text |Cite
|
Sign up to set email alerts
|

Automated Learning Setups in Automata Learning

Abstract: Test drivers are an essential part of any practical active automata learning setup. These components to accomplish the translation of abstract learning queries into concrete system invocations while managing runtime data values in the process. In current practice test drivers typically are created manually for every single system to be learned. This, however, can be a very time-consuming and thus expensive task, making it desirable to find general solutions that can be reused. This paper discusses how test dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The interaction with real-life systems and the construction of application-specific learning setups remain as challenges for the automata learning community despite their application in different scenarios over the years [24,42,43]. In this case study, we successfully demonstrated the use of active automata learning in the context of embedded automotive software implemented in MATLAB, a new application area.…”
Section: Interaction With the Sulmentioning
confidence: 96%
See 2 more Smart Citations
“…The interaction with real-life systems and the construction of application-specific learning setups remain as challenges for the automata learning community despite their application in different scenarios over the years [24,42,43]. In this case study, we successfully demonstrated the use of active automata learning in the context of embedded automotive software implemented in MATLAB, a new application area.…”
Section: Interaction With the Sulmentioning
confidence: 96%
“…In [55], automata learning is used to learn embedded software programs of printers. Though such research indicates the use of active automata learning for real-life systems, challenges exist to broaden its impact for practical use [24,42,43]. There are very limited examples on the use of active automata learning in an automotive context [34,54] and it is yet to find its place in automotive software development.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In [47], automata learning is used to learn embedded software programs of printers. Though such research indicates the use of active automata learning for real-life systems, challenges exist to broaden its impact for practical use [29,48,49]. There are very limited examples on the use of active automata learning in an automotive context [50,51] and it is yet to find its place in automotive software development.…”
Section: Related Workmentioning
confidence: 99%
“…Starting with the construction of application-specific test drivers by hand, it is discussed how a generic test driver can be employed by means of configuration. This configuration can be (semi-)automatically created by analysis of the target system's interface [14]. -Challenge E: Here we illustrate how a more global view of the learning process that more closely coalesces the two intertwined learning phases of model construction and model validation improves both, intuition and efficiency.…”
Section: Motivationmentioning
confidence: 99%